7-Chloro-4-[(E)-2-(2-methoxybenzylidene)hydrazin-1-yl]quinoline monohydrate - de Souza, M.V.N.; Howie, R.A.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V.; Kaiser, C.R. (International Union of Crystallography, 2010)
In the title hydrate, C17H14ClN3O center dot H2O, the dihedral angle between the quinoline fused-ring system and the benzene ring is 13.4 (2)degrees and the conformation about the C=N bond is E. In the crystal, N-h-H center dot center dot center dot O-w and O-w-H center dot center dot center dot N-q (h = hydrozone, w = water and q = quinoline) hydrogen bonds generate a two-dimenstional network in the ac plane. A weak C-H center dot center dot center dot O interaction helps to consolidate the packing.